The Investigation of a Patient with an Unusual Coagulation Defect - Gomes, Emiliano L.; Calicchio, Therezinha R.; Biggs, Rosemary (Thrombosis and Haemostasis, 1961)
1. The coagulation defect of a patient whose blood contains an inhibitor is described.2. The inhibitor lengthens the clotting time of plasma in the presence of weak thromboplastin and also interferes with the mechanism of glass contact activation.3. It is suggested that the inhibitor is similar to those which occur in the blood of patients with disseminated lupus erythematosus.